Implementation of Pancasila Democratic Values in the Life of the Nation and State - Atika Nafisah; Febriani Aulia; Ismawati (Lembaga Studi Agama dan Masyarakat Aceh, 2025)
The values contained in Pancasila include; religious values, kinship, harmony, populism, and justice. In addition, democratic values; the values of people's sovereignty, the rule of law, the guarantee of freedom, civil supremacy and equality of political rights. This research is a literature study (literature research) is a research that critically examines ideas, knowledge, findings in literature, field findings and documents, with a descriptive qualitative method. This research uses the perspective of Pancasila. The results of this study reveal the importance of implementing Pancasila democratic values in the life of the nation and state comprehensively, so as to create a clean government and a democratic system that is just and creates social welfare. The results of the study show that (1) The implementation of democratic values is carried out by including democratic values in the syllabus and learning implementation plan including tolerance, cooperation, freedom of opinion, mutual respect and trust. (2) The supporting factors are learning facilities, school culture and school leadership. The inhibiting factors are reduced parental support, the community environment, and personal differences. (3) The solution is parental awareness to pay attention to their children, community involvement, and establish good communication with students.